Assessment of myocardial viability using coronary zero flow pressure after successful angioplasty in patients with acute anterior myocardial infarction. Issue 1 (1st January 2003) - Shimada, K; Sakanoue, Y; Kobayashi, Y; Ehara, S; Hirose, M; Nakamura, Y; Fukuda, D; Yamagishi, H; Yoshiyama, M; Takeuchi, K; Yoshikawa, J
Abstract : Objectives: To investigate the relation between coronary flow reserve (CFR), coronary zero flow pressure (Pzf), and residual myocardial viability in patients with acute myocardial infarction. Designs: Prospective study. Setting: Primary care hospital. Patients: 27 consecutive patients with acute anterior myocardial infarction. Main outcome measures: 18 F-fluorodeoxyglucose (FDG) positron emission tomography (PET) was used in 27 patients who underwent successful intervention within 12 hours of onset of a first acute anterior myocardial infarction. Within three days before discharge they had < 25% stenosis in the culprit lesion as determined by angiography 24 (3) days after acute myocardial infarction. Pzf and the slope index of the flow-pressure relation (SIFP) were calculated from the simultaneously recorded aortic pressure and coronary flow velocity signals at peak hyperaemia.%FDG was quantified by comparing FDG uptake in the infarct myocardium with FDG uptake in the normal myocardium. Results: There was a correlation between %FDG and CFR, where y = −1.477x + 62.517, r = −0.072 (NS). There was also a correlation between %FDG and SIFP, where y = −0.975x + 60.542, r = −0.045 (NS), and a significant correlation between %FDG and Pzf, where y = −0.98x + 85.108, r = −0.696 (p < 0.001). Conclusions: CFR does not correlate with FDG-PET at the time of postreperfusion evaluation of residual myocardial viability. The parameter that correlates best with residual myocardial viability is Pzf and this may be a useful index for predicting patient prognosis.